FarmDrive, a win-win system - Bosire, Peris (Technical Centre for Agricultural and Rural Cooperation, 2015)
African smallholder farmers face a recurring problem of access to finance and credit. Financial institutions, for their part, do not have access to many potential customers, considered as too risky. Young Kenyan computer scientists have developed FarmDrive, an application that aims to promote access to credit and financial services for smallholder farmers. Banks remain to be won over, but the project is on track